Genetically predicted immune cells mediate the association between gut microbiota and autoimmune liver diseases - Zhang, Jikang; Hu, Yiqi; Xu, Jin; Shao, Hua; Zhu, Qingping; Si, Hao (Frontiers in Microbiology, 2024)
BackgroundIncreasing evidence suggests an association between gut microbiota and Autoimmune Liver Diseases (AILDs). However, causal inference remains controversial due to confounding bias in observational studies. Additionally, there is currently no clear evidence indicating that immune cells act as intermediate phenotypes in the pathogenesis of AILDs. This study utilizes the Mendelian Randomization (MR) method to investigate the causal relationships among gut microbiota, immune cells, and AILDs.MethodsInitially, we conducted a two-sample MR analysis to predict the causal relationships among 412 gut microbiota, 731 immune phenotypes, and AILDs. Subsequently, a series of sensitivity analyses were performed to validate the initial MR results and reverse MR analysis was conducted to exclude reverse causality. Finally, a two-step MR analysis was utilized to quantify the proportion of the impact of gut microbiota on AILDs mediated by immune cells.ResultsFollowing rigorous MR analysis, our findings indicate that increased involvement of the gut microbiome in the superpathway of L-tryptophan biosynthesis is positively associated with an elevated risk of Autoimmune Hepatitis (AIH). The effect is partially mediated by the CD14+ CD16+ monocyte Absolute Count, which accounts for 17.47% of the total effect. Moreover, the species Ruminococcus obeum appears to mediate the development of Primary Sclerosing Cholangitis (PSC) through CD62L-CD86+ myeloid Dendritic Cell %Dendritic Cell, contributing to 32.47% of the total observed effect.ConclusionOur study highlights the potential mediating mechanisms of immune cells in the causal relationship between the gut microbiome and AILDs. These insights provide a foundation for developing preventive strategies for AILDs in clinical practice.